2022
DOI: 10.1002/aenm.202103186
|View full text |Cite
|
Sign up to set email alerts
|

Edge‐Rich Multidimensional Frame Carbon as High‐Performance Electrode Material for Vanadium Redox Flow Batteries

Abstract: The low electrocatalytic activity of pristine graphite felt (GF) electrodes toward V(II)/V(III) and V(IV)/V(V) redox couples is a major concern in vanadium redox flow batteries (VRFBs). For overcoming this challenge, herein a novel composite electrode is proposed comprising of two components: multidimensional frame carbon (MFC) derived from edge‐rich carbon and GF that serves as the frame for the in situ growth of MFC. The high electrocatalytic activity, rapid charge migration, and reduced local current emanat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…In each spectrum, the D band (1335 cm −1 ) and G band (1581 cm −1 ) represent disordered carbon and graphitic carbon, respectively, in the lattice structure. 48 The G band in MX-5@PCNF is more intense than the G band in pristine carbon nanofibers (CNFs) carbonized at 700 °C. Furthermore, we observed that the I D / I G ratio of MX-5@PCNF ( I D / I G = 0.99) is lower than the I D / I G ratio of CNF ( I D / I G = 1.15), which signifies a higher degree of graphitization in MX-5@PCNF than in CNF.…”
Section: Resultsmentioning
confidence: 99%
“…In each spectrum, the D band (1335 cm −1 ) and G band (1581 cm −1 ) represent disordered carbon and graphitic carbon, respectively, in the lattice structure. 48 The G band in MX-5@PCNF is more intense than the G band in pristine carbon nanofibers (CNFs) carbonized at 700 °C. Furthermore, we observed that the I D / I G ratio of MX-5@PCNF ( I D / I G = 0.99) is lower than the I D / I G ratio of CNF ( I D / I G = 1.15), which signifies a higher degree of graphitization in MX-5@PCNF than in CNF.…”
Section: Resultsmentioning
confidence: 99%
“…Y. G. Guo et al also proposed a novel edge-rich multidimensional framework carbon (MFC) composite electrode composed of carbon nanoparticles (0D), carbon nanosheets (2D) and continuous carbon networks (3D). [67] The MFC composite electrode readily absorbed vanadium ions and acquired more reaction sites in the multi-dimensional structure, which not only exhibited high electrocatalytic activity for V 2 + /V 3 + and VO 2 + / VO 2 + redox couples, but also hindered the hydrogen evolution reaction. As shown in Figure 5(g-k), J.K. Kim et al fabricated porous carbon nanofibers (PCNFs) as VFB electrodes by electrospinning.…”
Section: Optimize Structural Designmentioning
confidence: 99%
“…[14] Particularly, vanadium redox flow batteries (VRFBs), which use same element as redoxactive species for positive and negative half-cells, have attracted wide attention in the past two decades primarily because of the elimination of cross-contamination issue. [15][16][17] Porous electrode, where convection-diffusion-reaction processes simultaneously occur, is one of the vital components of VRFBs, significantly affecting the cell performance. [18][19][20] Present-ly, the most investigated and used electrodes in VRFBs are carbon fibrous electrodes, including carbon felt, cloth and paper.…”
Section: Introductionmentioning
confidence: 99%